Educating persons with special needs in the 21st century through appropriate educational programmes for relevance and development in Nigeria (2019)
Education is a tool for National development. The development of any nation technologically, socially, politically and economically is largely dependent on the education the citizens. Every member of each nation. notwithstanding the age, background, sensory, physical or psychological impairment, should have equal access to education in order to achieve the goal of education for all. This paper therefore, examined education as a tool for empowering persons with special needs, educating persons with special needs in the 21sl Century for relevance and development, inclusive education as appropriate educational Programme for persons with special needs, factors affecting successful implementation of inclusive education for persons with special needs and vocational/entrepreneurship education for persons with special needs. Persons with special needs should be given sense of belonging in the society by empowering them educationally and vocationally.